Angiogenic and Antiangiogenic Factors in Preterm Neonates Born to Mothers with and without Preeclampsia - Hentges, Cláudia R.; Silveira, Rita C.; Procianoy, Renato S. (American Journal of Perinatology, 2015)
Background Angiogenic and antiangiogenic factors are altered in pregnant women with preeclampsia (PE), but the pattern of expression of these factors in their newborns remains unknown.Objective This study aims to measure vascular endothelial growth factor (VEGF) and soluble fms-like tyrosine kinase 1 (sFlt-1) levels in preterm neonates born to mothers with PE.Methods Neonates with birth weight < 2,000 g and gestational age ≤ 34 weeks were included and divided into the following two groups: born to mothers with PE and without PE. Blood was collected from neonates within the first 72 hours of life. VEGF and sFlt-1 levels were measured using the enzyme-linked immunosorbent assay method.Results A total of 88 neonates were included (37 born to mothers with PE and 51 born to mothers without PE), with a mean gestational age of 29.12 ± 2.96 weeks and birth weight of 1,223.80 ± 417.48 g. In the multivariate analysis, VEGF was 80% lower and sFlt-1 was 13.48 times higher in the group with PE. sFlt-1 concentration was higher in neonates small for gestational age (SGA) than in those appropriate for gestational age.Conclusion Higher sFlt-1 and lower VEGF levels in the group with PE, as well as higher sFlt-1 levels in SGA neonates, reflect a predominance of antiangiogenic mechanisms in PE and growth restriction.
Keywords: angiogenic factors; preeclampsia; prematurity; VEGF; sFlt-1; antiangiogenic factors